Nursing assistants’ knowledge, attitudes and training needs regarding urinary incontinence in nursing homes: a mixed-methods study - Lulu Liao; Hui Feng; Jingjing Jiao; Yinan Zhao; Hongting Ning (BMC Geriatrics, 2023)
Abstract Background Urinary incontinence is an increasingly common problem, especially among older people in nursing homes. Nursing assistants are the leading workforce in nursing homes, and their knowledge and attitudes regarding urinary incontinence have garnered considerable attention in the context of aging in China. However, most previous studies on this issue have focused on registered nurses. This study aimed to explore nursing assistants’ knowledge, attitudes and training needs with regard to urinary incontinence. Methods We conducted a two-part mixed-methods study. After institutional manager approval, we surveyed the knowledge and attitudes of 509 nursing assistants regarding urinary incontinence. We carried out semi-structured interviews with 40 nursing assistants to elicit detailed information on training needs. Results In general, knowledge about urinary incontinence was poor (14.00 ± 4.18), although attitudes were primarily positive (35.51 ± 3.19). Most nursing assistants were very willing to learn more about urinary incontinence (93.9%, 478/509), but time constraints and low educational background may be barriers to learning motivation. The three preferred training styles among nursing assistants were face-to-face guidance from a mentor, training combining theory with practice, and online video training. Conclusions Chinese nursing assistants had poor knowledge but positive attitudes toward urinary incontinence. Facility managers should focus on developing training and learning mechanisms regarding urinary incontinence. It is important to adopt diverse training styles according to the actual situation of nursing homes.